Impact of Different Sensory Stimuli on Presence in Credible Virtual Environments - Goncalves, Guilherme; Melo, Miguel; Vasconcelos-Raposo, Jose; Bessa, Maximino (IEEE transactions on visualization and computer graphics, 2020)
Multiple factors can affect presence in virtual environments, such as the number of human senses engaged in a given experience or the extent to which the virtual experience is credible. The purpose of the present work is to study how the inclusion of credible multisensory stimuli affects the sense of presence, namely, through the use of wind, passive haptics, vibration, and scent. Our sample consisted of 37 participants (27 men and 10 women) whose ages ranged from 17 to 44 years old and were mostly students. The participants were divided randomly into 3 groups: Control Scenario (visual and auditory - N = 12), Passive Haptic Scenario (visual, auditory, and passive haptic - N = 13) and Multisensory Scenario (visual, auditory, wind, passive haptic, vibration, and scent - N = 12). The results indicated a significant increase in the involvement subscale when all multisensory stimuli were delivered. We found a trend where the use of passive haptics by itself has a positive impact on presence, which should be the subject of further work.